The Impact of Digital Financial Literacy on Financial Behaviour and Financial Well-Being of Rural Millennials - Sri Hardianti Sartika; Astri Srigustini; Allicia Deana Santosa (Jurnal Inovasi Pendidikan Ekonomi, 2026)
This study investigates the role of digital financial literacy in shaping the financial well-being of millennials residing in rural areas of West Java, with financial behaviour serving as a mediating variable. Employing a quantitative explanatory survey design, data were collected from 315 millennial respondents and analysed using descriptive statistics and path analysis. The findings reveal that digital financial literacy exerts a significant but negative effect on both financial behaviour and financial well-being. Financial behaviour is also found to significantly influence financial well-being, indicating that higher engagement with financial activities does not necessarily translate into improved financial outcomes. These results suggest that increased exposure to and understanding of digital financial services may encourage consumptive practices and over-reliance on digital credit when not accompanied by prudent financial management. The study highlights that digital financial literacy alone is insufficient to enhance financial well-being unless it is integrated with responsible financial behaviour and effective risk awareness. Consequently, targeted financial education and stronger regulation of digital financial services are essential to improving the long-term financial well-being of rural millennials.